Characterization Of Gan Nanowies Grown By Thermal Evaporation On Different Substrates And The Study Of Their Capability As A Solar Cell - Shekari, Leila (2013)
In this study, Gallium Nitride (GaN) nanowires (NWs) were grown on different substrates, such as Silicon (Si) (111) and (100) either with or without Gold (Au) coating, Porous Si (PS), Porous GaN (PGaN) and Porous ZnO (PZnO), using the Thermal Evaporation method. SEM images of the synthesized GaN NWs displayed an overview of apparently high density and straight well-ordered GaN NWs on the Si (111) substrate compare to GaN NWs on Si (100) substrate. The SEM images of GaN NWs on Si (100), Au-coated Si (111) and PZnO indicated that the density of NWs was apparently less than that in samples of other substrates.